2017
DOI: 10.17509/ijal.v7i2.8126
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Feedback Provision in Improving Pre-Service Teachers’ Competence

Abstract: Studies on potentials of feedback over English language teaching seem not to have not been wellrevealed, including studies on the use of feedback to improve English pre-service teachers' competence. The present study investigates to what extent a multimodal feedback can influence preservice teachers' teaching, and which teaching aspects are influenced. Twenty five pre-service teachers taking Microteaching Course served as respondents supervised by a course advisor. The data were collected by teacher observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
(29 reference statements)
1
12
0
1
Order By: Relevance
“…Rather than saying it explicitly, the participant preferred to tell it implicitly, so the students can be more critically reflected on their own errors or mistakes. Yusuf et al (2017:) concluded that self-reflective thinking is needed for pre-service teachers to develop their teaching competence.…”
Section: Discussion Lecturer's Politeness Strategy With Its Implemenmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than saying it explicitly, the participant preferred to tell it implicitly, so the students can be more critically reflected on their own errors or mistakes. Yusuf et al (2017:) concluded that self-reflective thinking is needed for pre-service teachers to develop their teaching competence.…”
Section: Discussion Lecturer's Politeness Strategy With Its Implemenmentioning
confidence: 99%
“…In addition, an interview session was conducted to investigate if there was any consideration of the participant to perform politeness strategy by recognizing the students multicultural background. Yusuf et al (2017) found that there are several dimensions of feedback, and one of them is socio-affective. This idea also supported with the research conducted by Mahmud (2019) who found that in order to know the practicing politeness in the classroom it need cross cultural context of politeness.…”
Section: Lecturer's Considerations On Students' Multicultural Backgromentioning
confidence: 99%
“…Pengamatan dilakukan oleh peneliti langsung dengan berbekal pedoman observasi yang telah dipersiapkan terlebih dahulu. Hasil pengamatan mengenai sarana dan prasarana pada perkuliahan micro teaching dapat disajikan pada tabel berikut: Tabel 1.Hasil Observasi Sarana Prasana Pada Perkuliahan MicroTeaching antara anteseden, transaksi, dan outcome, dan menemukan kesesuaian (congruence) antara intents dan observations(Stake, 1973). Suatu data dari sebuah evaluasi kurikulum dikatakan sesuai, jika apa yang telah diinginkan benar-benar terjadi.…”
unclassified
“…During this step, they got valuable feedback and suggestions from their advisors by applying a good relationship between them. In this stage, multimodal feedback provision could improve students' competence when it is integrated with content, interpersonal relationship, and management (Yusuf et al, 2017).…”
Section: Stage Of Conducting Researchmentioning
confidence: 99%